2010
DOI: 10.1177/0886260509354517
|View full text |Cite
|
Sign up to set email alerts
|

Intimate Partner Violence During Pregnancy: A Pilot Intervention Program in Lima, Peru

Abstract: This pilot study examined the effectiveness of standard care and an empowerment intervention for abused pregnant women. Severe psychological abuse was most prevalent (42.2%) among this sample of women. Compared with women in the standard care group at the post-intervention survey, women in the empowerment group were more likely to hide money (44.6% vs. 34.3%), establish a code with family or friends (19.6% vs. 16.2%), ask neighbors to call police if violence began (6.9% vs. 1.0%), had available bank account nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
180
0
3

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(192 citation statements)
references
References 39 publications
9
180
0
3
Order By: Relevance
“…A significant reduction in IPVv prevalence rates over time, regardless of the type of treatment, is consistent with findings from other intervention studies conducted in a variety of social and health settings. Another important finding is that there appear insignificant differences between intervention and control groups, which is in line with that of Cripe et al [22], Zlotnick et al [72], Curry et al [73], Humphreys et al [74]. However, some RCTs, which evaluate home visit programs [27,69,75,76] and typically address several issues (e.g.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…A significant reduction in IPVv prevalence rates over time, regardless of the type of treatment, is consistent with findings from other intervention studies conducted in a variety of social and health settings. Another important finding is that there appear insignificant differences between intervention and control groups, which is in line with that of Cripe et al [22], Zlotnick et al [72], Curry et al [73], Humphreys et al [74]. However, some RCTs, which evaluate home visit programs [27,69,75,76] and typically address several issues (e.g.…”
Section: Discussionsupporting
confidence: 64%
“…In recent years, research across the western world and increasingly in low-and middle-income countries has generated growing evidence that experiencing violence (as victim as well as perpetrator) in the perinatal period is related to risk behaviour and detrimental effects on the physical and mental health of women, men and children [21][22][23][24][25][26][27][28]. A cohort study of women aged 18-44 years suggested that IPVv was responsible for 7.9% of the overall burden of disease, which was more prominent than other risk factors such as high blood pressure, tobacco, and obesity [29,30].…”
Section: Introductionmentioning
confidence: 99%
“…Yet, other studies implementing interventions did not find significant differences in IPV between the intervention and control groups however these were pilot studies. 98,99 Furthermore, in one of the pilot studies, the majority of the sample reported ''severe'' abuse, which related to greater impairment. Thus, the impact of a brief intervention may be limited in women with severe forms of abuse.…”
Section: Discussionmentioning
confidence: 98%
“…The empowerment approach also yielded some significant results in a subsequent study conducted in Peru by Cripe et al (2010). The study, which involved 220 women randomly assigned to either empowerment treatment or a control group receiving standard care, consisted of asking about abuse and offering program referrals.…”
Section: Intervention During Pregnancymentioning
confidence: 99%
“…Finally, we think it worthy of note that several studies that we have discussed in this section have suggested that the presence of an IPV assessment may itself contribute to reducing or halting future abuse by simply making women aware of this concern (Cripe et al, 2010;McFarlane et al, 2000;Tiwari et al, 2005); therefore, future research should seek to distinguish between outcomes prompted by screening alone and those that can be credited to specific intervention programs that could be generalized to multiple groups and locations.…”
mentioning
confidence: 99%